Development of Education from Junior High upto Secondary Level in Jangipur Municipality of Murshidabad District, West Bengal- An Appraisal - Ayan Das Gupta, (AG Volumes, 2022)
The present paper will throw focus on the status and stature of Education from Junior High upto the Secondary level in the Urban Local Body of Jangipur of Murshidabad District, West Bengal. Education is considered to be the backbone of human society and the primary level education is actually the base of all education. It helps the children to be familiar with the academic environment gradually and thereafter comes the turn of junior high education. The junior high education upto 8th standard helps the student to come in close touch with secondary education in a very slow manner. Here the gender based distribution of the literate students has been manifested along with the establishment of close relationship with income level and that of educational attainment. Quantitative discussion on the level of education in Jangipur Municipality has not only been highlighted in the current academic endeavour but also at the same time the scenario of school dropout has also been ruled out through perception study. Midday meal now serves as a lucrative attraction to the students turning up from the poor and pecuniary condition and hence the context of serving of midday meal has also been traced out over here. From study of this paper, the target audience will be able to get a clear picture of education among the children and adolescent boys and girls in the nodal agency of Jangipur.